Gastrointestinal Stromal Tumor (GIST) in the Rectum: A Rare Location - Mitre-Reyes, Nadab David; Morales-Chomina, Yulia Angélica; Mendoza Namur, Luz del Carmen; Guerrero-Gomez, Alan; Fuentes-Calvo, Kevin Joseph; Rojas-Illanes, Moises Freddy (Journal of Coloproctology, 2025)
Gastrointestinal stromal tumor (GIST) is a rare condition that originates in the cells of Cajal and constitutes the most frequent type of malignant mesenchymal tumors in the gastrointestinal tract. Although their incidence is low, GISTs are most common in the stomach and small intestine, although they can occur in other areas, such as the rectum. Although no specific risk factor has been identified, certain genetic conditions such as neurofibromatosis type I increase the likelihood of developing a GIST. Symptoms may vary depending on the location of the tumor and include early satiety, abdominal distention, gastrointestinal disturbances, and bleeding.The diagnosis is usually made incidentally during radiologic or endoscopic studies and is confirmed by immunohistochemistry studies that identify mutations in cluster of differentiation 117 (c-KIT) and platelet-derived growth factor receptor kinase alpha (PDGRF-α) receptors. These tumors are resistant to conventional chemotherapy and radiotherapy.Management of the disease preferably involves surgical resection, aiming for complete removal of the tumor. Prognosis after surgery depends on the size of the tumor and its mitotic activity. Periodic follow-up with imaging tests is recommended for several years after resection.In advanced cases, treatment may include therapy with imatinib, a tyrosine kinase inhibitor that has demonstrated efficacy in GISTs. Primary resistance to treatment can be a challenge, and in advanced rectal tumors, several surgical options can be considered, although resection can be difficult due to the location of the tumor and its adherence to the pelvic floor.Despite curative resection, recurrence and distant metastasis, especially to the liver, are major concerns, with a reduced median survival in patients with advanced disease.
Keywords: Gastrointestinal Stromal Tumor; GIST; rectum; surgical resection; immunohistochemistry